Transgene-product expression levels in genetically engineered breeding stacks are equivalent to those of the single events. Issue 1 (2nd January 2019) - De Cerqueira, Denise T.; Fast, Brandon J.; Silveira, Alessandra C.; Herman, Rod A.
ABSTRACT: Transgene product expression levels are measured in genetically engineered (GE) crops containing single transformation events and the measured expression levels are then utilized in food, feed, and environmental safety assessments as part of the requirements for de-regulation of the event. Many countries also require measurement of expression levels and safety assessments for GE breeding stacks, even though the breeding stacks are composed of single events that have been previously assessed. Transgene product expression levels were measured in tissues of maize, soybean, and cotton breeding stacks and each of their component single events. Expression levels in the breeding stacks were plotted against expression levels in the single events to quantify the ability of the single events to predict transgene product expression levels in the breeding stacks. These results indicate that transgene product expression levels in single events are a reliable indicator of expression levels in breeding stacks. Based on these results it is concluded that safety assessments for breeding stacks can be conducted using transgene product expression levels from single events.